Chemical Characterization of Phytochemicals of Cucurbitaceae Family by Gas Chromatography – Mass Spectroscopy - Mahesh Doshi, Gaurav; P. Kanade, Preeti; Vilasrao Nalawade, Vivek; Kashinath Chaskar, Pratip (Current Traditional Medicine, 2017)
Background: Traditionally plants are being used as an important source of medicines since ancient era. Cucurbit seeds have been used as nutritious snacks as they are rich in phytonutrients and have a wide arena of ethnopharmacological relevance. Objective: Present research study was designed to identify the phytochemicals in n-hexane seed extracts of Cucurbita pepo (CP), Cucumis melo (CM), Cucumis sativus (CS) belonging to family Cucurbitaceae by hyphenated techniques such as Gas Chromatography – Mass Spectroscopy (GC-MS). Method: Soxhlet extraction of Cucurbita pepo , Cucumis melo, Cucumis sativus seeds was done using n-hexane as solvent and GCMS analysis was performed using Joel, USA with model of Accu Time of Flight GCV. Result: The components were identified by matching mass spectra with mass spectrum libraries. There were six, eight and nine different compounds analysed from CP, CM and CS extracts respectively. The components present were Palmitic acid; 17-Octadecynoic acid; Z-7-Hexadecenal; Squalene; 9,12-Octadecadienoic acid (Z,Z)-; γ-Tocopherol; 17- Octadecynoic acid; 1-Heptatriacotanol; Cholest-22-ene-21-ol-3,5-dehydro-6-methoxy-, pivalate; 9,10-Secocholesta-5,7,10(19)-triene-3,24,25-triol,(3β,5Z,7E)-; 1-Naphthalenepropanol,α-ethyldecahydro-α,5,5,8a-tetramethyl-2-methylene-[1S-[1α(Sx),4αβ,8αα)]]-; 9,12,15-Octadecatrienoic acid, 2-(acetyloxy)-1-[(acetyloxy)methyl]ethyl ester,(Z,Z,Z)-; 1-Heptatriacotanol; Ergosta-7,22-dien-3-ol,(3β,5α,22E)-; Stigmaterol; D:C-Friedours-7-en-3-one in CP, CM and CS seeds extracts respectively. Conclusion: From the results obtained it is concluded that Cucurbita pepo , Cucumis melo, and Cucumis sativus contain various phytochemicals, justifying their use for various human ailments.
Keywords: γ-Tocopherol